Teacher’s Strategies in Teaching Speaking by Using Video Media - Yenny Rahmayanti; Arifin Syamaun; Burhansyah Burhansyah (Research in English and Education Journal, 2017)
The design of this study is descriptive qualitative research. It focuses on how the teacher applies teaching strategies by using video media to improve the students’ speaking ability. The research was conducted at the second grade of SMAN Modal Bangsa, Aceh Besar. To obtain the data, the researcher used interview guide and observation checklist. It was found that the teacher applied the three teaching strategies categorized by Bouhard (2005) and Chamont Omelly (1994), meta-cognitive strategies, cognitive strategies, and socio affective strategies, in teaching speaking by using video media. The result of this study indicates that the strategies applied by the teacher were essential to arrange the teaching learning process efficiently, to contribute information to the students, and to facilitate the students to practice the language in group. Besides, based on the interview and observation, it was found that video media is effective to stimulate students’ learning as they felt enthusiastic to learn as the video was played. Also, video is easy to use and is accessible for free download on the internet; thus, it was easier for the teacher to make preparation for the teaching learning activity. In the end, the result of this study indicates the pedagogical implications for English teachers in teaching EFL by using video as media and can be used as the reference for other researchers who aim to conduct similar studies.